Pemanfaatan e-marketplace sebagai Bentuk Pemberdayaan UMKM dalam Menghadapi Revolusi Industri 4.0. - Almira Shabrina (Connected: Jurnal Ilmu Komunikasi, 2021)
The era of industrial revolution 4.0 which emphasizes the use of internet of things in the industrial sector is an opportunity and a threat to Indonesia. The era of industrial revolution 4.0 can be an opportunity to do business effectiveness, but on the other hand threatens the loss of job availability by replacing human resources using machines. To anticipate this, the government made a roadmap for making Indonesia 4.0 as an effort to prepare for the presence of this industrial revolution 4.0, one of which focused on empowering UMKM. The author will discuss a little about how e-marketplace can be used as a form of empowering UMKM to face this industrial revolution 4.0.